2022
DOI: 10.1002/cpz1.496
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity Evaluation of Nanomaterials Using C. elegans: Survival, Locomotion Behaviors, and Oxidative Stress

Abstract: Nanomaterials are broadly used in a variety of industries and consumer products. However, studies have demonstrated that many nanomaterials, including metal-containing nanoparticles and nanoplastics, have neurotoxic effects. Caenorhabditis elegans (C. elegans) is a widely used model organism with numerous advantages for research, including transparency, short life span, wellcharacterized nervous system, complete connectome, available genome, and numerous genetic tools. C. elegans has been extensively used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Locomotion behaviors such as body bending and head thrashing were thus measured to reect the functional state of motor neurons. 40 We found that CSP-DBO up to 40 mM did not signicantly affect body bend or head thrash of the worms (Fig. S12 †), indicating that CSP-DBO had no obvious neurotoxic effect in C. elegans.…”
Section: Dynamic Tracking Of Morphological Changes Of the Plasma Memb...mentioning
confidence: 87%
“…Locomotion behaviors such as body bending and head thrashing were thus measured to reect the functional state of motor neurons. 40 We found that CSP-DBO up to 40 mM did not signicantly affect body bend or head thrash of the worms (Fig. S12 †), indicating that CSP-DBO had no obvious neurotoxic effect in C. elegans.…”
Section: Dynamic Tracking Of Morphological Changes Of the Plasma Memb...mentioning
confidence: 87%
“…The somata of HSN neurons were located close to the vulva, whereas dendritic processes extended along the ventral nerve cord to the head (Figure 1A; inset 3). After exposition to silica NPs, the fluorescent signal of all dendritic processes changed to dotted patterns (Figure 1B; insets [4][5][6] that usually indicate dendritic beading and neurodegeneration. Quantification in young and middle-aged C. elegans showed that nano silica-induced a significant age-related increase in neurodegeneration in the serotonergic neurons ADF, HSN and NSM compared to mock-exposed controls and reporter nematodes that were exposed to BULK silica particles with a larger diameter (Figure 1C).…”
Section: Chronologic Sequence Of Nano Silica-induced Degeneration In ...mentioning
confidence: 99%
“…As beading precedes the retraction of dendrites to the soma and usually heralds neuronal death, early and specific beading of dopaminergic PDE neurons may serve as a disease model that mimics the death of specific dopaminergic neurons in PD [7,17]. The insets show blow-ups of the ADF dendrites, the NSM processes and the HSN axons (1)(2)(3)(4)(5)(6). A discontinuous punctate fluorescence pattern was categorized as neurodegeneration.…”
Section: Chronologic Sequence Of Nano Silica-induced Degeneration In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, C. elegans has been applied as a valuable model to evaluate the neurotoxicity of various chemicals because of the conservation of the biocharacteristics of neurotransmitters of the human in the worm. [29,31,[41][42][43][44] Thus, we employed C. elegans as the model organism for the neurotoxicology evaluation of SA-CsPbBr 3 PeQDs. The array of endpoints consisting of locomotive behaviors, forging behavior, pharyngeal pumping, brood size, and lifespan was performed to provide information on the potential risks of PeQDs in the neural system.…”
Section: Effects Of Sa-cspbbr 3 Peqds On Behaviors and Pharyngeal Pum...mentioning
confidence: 99%